A SEM-X-Ray assisted experimental approach for the determination of mechanical and thermal load induced damage in MMCs - Victor N. Kytopoulos; Emilios Sideridis; John Venetis; Chrysoula Riga; Alexandros Altzoumailis (Fracture and Structural Integrity)
An experimental technique is presented to evaluate mechanical and thermal load-induced microstructural damage, based on the Electron Probe Micro-Analysis (EPMA) principle, by which certain ana¬lyti¬cal potentialities of Scanning Electron Micro¬scopy (SEM) are used. The aim of the study is to apply this technique in the case of metal matrix composites (MMCs). Based on earlier findings it is shown that by this technique the damage-con¬trolled micro¬¬structural integrity distribution ahead of an edge-notch under tension is deter¬mined with sufficient reliability. To demonstrate this fact two MMCs were tested. Dog-bone specimens with an edge notch were subjected to slow tension up to their ultimate stress, the loading process was terminated and the EPMA technique was applied. The procedure was also applied after sudden cooling of the specimens by immersion in liquid hydrogen. It is shown that the MMC with larger differences between the elastic and plastic constants of the inclusion and the matrix exhibit increased prone¬ness to mechanical and thermal load-induced damage. The findings obtained are discussed on the basis of the dominating com¬bined influence of macro-microscopic mechanical and thermo-elastic stress concentration processes on the matrix-particle interfacial fracture strength